Fast Block Partitioning Algorithm for HEVC Based on Spatial Correlation and Image Texture - Yingbiao Yao; Xiaojuan Li (Dianxin kexue)
In order to reduce the intra coding complexity of HEVC, a fast block partitioning algorithm based on spatial correlation and image texture was proposed. Firstly, a concept of most possible depth range（MPDR）was proposed according to the correlation analysis of adjacent CTU depth range. Secondly, the difference between the current CTU texture and neighboring CTU texture was analyzed by detecting the dominant edge direction. According to the texture difference, the depth range of the current CTU was chose from MPDR and the origin range 0～3. Finally, a formula for texture complex threshold was formed by statistical calculation. Before CU coding, detect the texture complexity of the current CU by comparing the pixel variance and threshold, determine whether or not to skip the current unit coding calculation. Compared with HM13.0, experimental results reveal that the proposed algorithm can save about 20% computational complexity on average whereas the average bit rate increment is 0.84% and the decrement of PSNR is 0.04 dB.